GAMBARAN PERSEPSI PASIEN TERHADAP PERILAKU CARING PERAWAT DIRUANG RAWAT INAP PUSKESMAS TENAYAN RAYA - Cindy Lestari; Erwin Erwin; Sri Wahyuni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Caring behavior is the behavior that underlies the attitude, as well as the form of a nurse'sperformance in providing nursing services to her patients. Knowing th e description of the patient's perception of the caring behavior of nurses in the inpatient room. This study uses a simple quantitative descriptive design, with a total of 30 respondents using a total sampling technique. The instrument used in this study used a Caring Behavior Assessment (CBA) questionnaire that had been proposed from Yuliawati's research (2012) through validity and reliability tests. The analysis used is univariate analysis. This study explains the caring behavior of nurses in general get results as many as 21 patients (70%) in the medium category. Caring behavior was divided into 2 subvariables consisting of affective behavior and instrumental behavior, affective behavior got results as many as 25 patients (83,3%) in the medium category and instrumental behavior as many as 19 patients (63,3%) in the medium category. This study shows that the results of respondents in assessing the service of nurses are quite good, it is hoped that nurses can improve caring behavior towards patients tosupport the quality of services at the Puskesmas. Keywords: Perception, caring behavior, nurses.